2009
DOI: 10.1111/j.1651-2227.2008.01197.x
|View full text |Cite|
|
Sign up to set email alerts
|

High prevalence of cardio‐metabolic risk factors among adolescents with intellectual disability

Abstract: The prevalence of cardio-metabolic risk factors and poor cardio-vascular fitness was found to be high in this young population with intellectual disabilities. Measures should be taken to improve the health messages directed towards children and adolescents with intellectual disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
39
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 38 publications
7
39
0
2
Order By: Relevance
“…4-7 As in the general pediatric population, a steady decline in physical activity with age is observed. 8,9 Adverse health outcomes for youth with ID that have been consistently associated with low physical activity include poor cardiovascular fitness, 10,11 low muscular strength and endurance, 12 and high prevalence of overweight and obesity. 10,11,13,14 The underlying causes of low activity levels among youth with ID remain unclear, but a range of personal, social, environmental, and program-related variables likely create obstacles that restrict participation.…”
mentioning
confidence: 99%
“…4-7 As in the general pediatric population, a steady decline in physical activity with age is observed. 8,9 Adverse health outcomes for youth with ID that have been consistently associated with low physical activity include poor cardiovascular fitness, 10,11 low muscular strength and endurance, 12 and high prevalence of overweight and obesity. 10,11,13,14 The underlying causes of low activity levels among youth with ID remain unclear, but a range of personal, social, environmental, and program-related variables likely create obstacles that restrict participation.…”
mentioning
confidence: 99%
“…Our findings are consistent with earlier research, which reported a higher risk of diabetes in children with DDs (e.g. Wallén et al ., ; Rimmer et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Em relação à CA, que se associa à gordura visceral (intraabdominal) 10 , foi constatado que a maioria dos participantes apresentou risco cardiovascular aumentado ou muito aumentado, sendo mais evidente entre as mulheres e entre participantes com DI moderada. Os achados desta pesquisa corroboram com Wallen et al 14 , que identificaram um padrão aumentado de circunferência abdominal nos adolescentes com DI, e por Lin et al 22 , que observaram obesidade abdominal em 21% dos homens e 51,8% das mulheres tailandeses com DI.…”
Section: Conclusãounclassified